2020
DOI: 10.12944/crnfsj.8.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Low Ratio n-6:n-3 PUFA Reduces Body Fatness in Young Obese Balinese Women: A Randomized Study with Optimized Energy Regulation

Abstract: Background and Objectives: Obese Indonesians, including Balinese, are at higher risk of comorbidities like, CVD, diabetes, non-alcoholic fatty liver disease. Urban Balinese are changing their diet from traditional to fast foods and the like that are high in saturated fats. Nutritional modification, such as increasing n-3 PUFA content in the diet, may aid in managing body fat accumulation-related diseases. This study investigated the effects of supplementation of n-6:n-3 PUFA with ratio of 2:1 on body fat reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Weta and his colleagues, in an interventional study, reported that the reduction of body fat could be enhanced by supplementation with a high dose of a low omega-6/ omega-3 ratio; they documented a significant reduction of BMI, WC, CI, and LAP within the interventional group. (54) Extensively, a large base of evidence recommends a balanced intake of omega-3 and omega-6 to reduce the risk of obesity and its related NCDs. (19,52) Furthermore, Suara and his colleagues suggested that for obesity prevention, it is essential to increase the intake of omega-3/omega-6 to higher ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weta and his colleagues, in an interventional study, reported that the reduction of body fat could be enhanced by supplementation with a high dose of a low omega-6/ omega-3 ratio; they documented a significant reduction of BMI, WC, CI, and LAP within the interventional group. (54) Extensively, a large base of evidence recommends a balanced intake of omega-3 and omega-6 to reduce the risk of obesity and its related NCDs. (19,52) Furthermore, Suara and his colleagues suggested that for obesity prevention, it is essential to increase the intake of omega-3/omega-6 to higher ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Weta and his colleagues, in an interventional study, reported that the reduction of body fat could be enhanced by supplementation with a high dose of a low omega-6/omega-3 ratio; they documented a significant reduction of BMI, WC, CI, and LAP within the interventional group. ( 54 )…”
Section: Discussionmentioning
confidence: 99%